A predictive approach to simulating the forming of viscous textile composite sheet - Harrison, Philip; Yu, Woong-Ryeol; Wang, Jinhuo; Long, Andrew C.; Clifford, Michael J. (European Journal of Computational Mechanics, 2005)
A commercial Finite Element (FE) code is used to simulate the forming of a thermoplastic viscous textile composite sheet. The main success of this work is in combining two distinct models. The first is a rate and temperature dependent unit cell energy model, designed to predict the shear force – shear angle – shear rate response of viscous textile composites. The second is a non-orthogonal rate-independent constitutive model that has been implemented previously in the code. Both models are reviewed briefly and the method of combining these models in the code is described. Preliminary results of Picture Frame test simulations together with complex forming simulations are presented and discussed.